Tecnología en circuitos fotónicos integrados. - Pelli, Pablo N. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2016)
Fil. Pelli, Pablo N.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina